The Motivation Level Towards the Application of Google Apps Among Part-Time Students: A Case Study - Amiruddin, Mohd Hasril; Mahazir Ismail, Irwan; Razali, Nizamuddin; Ismail, Mohd Erfy; Doman, Noriyani; Abd. Samad, Noorazman; Abdul Rahim, Azwin Arif (Journal of Technical Education and Training, 2019)
The rapid development of technology nowadays has changed today’s education system, especially in facilitating teaching and learning, and increasing students’ motivation. The development in the area of applications such as google apps have positively impacted teaching fields as a medium to disseminate information and instructional strategies between a lecturer and students. However, students do not have a sense of motivation to learn a new learning environment that is based on technology. The aim of this study was to determine the level of students’ motivation towards google apps. This was a survey study using a set of questionnaire as the instrument. The data were analyzed using mean scores to determine the students’ level of motivation. These findings showed that the students’ motivation to use google apps were high accordingly in terms of Google Drive for attention, relevance, confidence and satisfaction; Google Form for attention, relevance, confidence and satisfaction; Google Spreadsheets for attention, relevance, confidence and satisfaction, while Google PowerPoint for attention, relevance, confidence and satisfaction. The findings helped to determine the appropriate google apps as instructional strategies to be applied in teaching and learning that would be able to increase the students’ motivation to learn. In general, this study supports the use of google apps in assisting learning process that can increase part-time students’ motivation.